2019
DOI: 10.1002/cne.24787
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cutaneous papillae in the sea lamprey (Petromyzon marinus L.): I. Neuroanatomy and physiology

Abstract: Molecules present in an animal's environment can indicate the presence of predators, food, or sexual partners and consequently, induce migratory, reproductive, foraging, or escape behaviors. Three sensory systems, the olfactory, gustatory, and solitary chemosensory cell (SCC) systems detect chemical stimuli in vertebrates. While a great deal of research has focused on the olfactory and gustatory system over the years, it is only recently that significant attention has been devoted to the SCC system. The SCCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 119 publications
(243 reference statements)
0
11
0
Order By: Relevance
“…The companion paper to this study has shown that lamprey SCCs on gill pores respond to dead trout water, amino acids and taurocholic acid in electrophysiological recording experiments (Daghfous et al, ). These responses suggest that the gill pore SCCs are useful during feeding.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The companion paper to this study has shown that lamprey SCCs on gill pores respond to dead trout water, amino acids and taurocholic acid in electrophysiological recording experiments (Daghfous et al, ). These responses suggest that the gill pore SCCs are useful during feeding.…”
Section: Discussionmentioning
confidence: 91%
“…planeri . While Baatrup and Døving () and Daghfous et al () have shown neural chemosensory responses in these gill papillae, it is possible that the lamprey SCC activity may also extend to nonneural signaling mechanisms. For example, chemicals emitted by bacteria stimulate a non‐neural antimicrobial innate immune defense response in mammalian SCCs (e.g., Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A comparison between adults and larvae revealed important developmental changes in Ucn3 expression, with new positive populations appearing in the striatum, torus semicircularis, isthmus and nucleus of the solitary tract after the metamorphosis. Transformation in the sea lamprey is complex, and in the nervous system, it largely affects the visual system including the eye and optic tectum [36][37][38][39][40][41], but also other neural systems such as the medial pallium, cutaneous sensory systems and the olfactory rosette [42][43][44]. Other body organs also suffer important anatomical and physiological changes during transformation to adapt adult lampreys to a new adult life-style (free and ectoparasitic life), which is very different from the blind, burrowing, water-filtering larvae [31].…”
Section: Discussionmentioning
confidence: 99%